Social Epistemology, the Reason of "Reason" and the Curriculum Studies - Thomas Popkewitz (Arizona State University, 2014)
Not-with-standing the current topoi of the Knowledge Society, a particular "fact" of modernity is that power is exercised less through brute force and more through systems of reason that order and classify what is known and acted on.  This article explored the system of reason that orders and classifies what is talked about, thought and act on in schooling.  The study of the system of reason in schooling is framed as social epistemology to consider the historically ordered, relational and socially embeddedness of knowledge as the political.  This entails exploring the "reason" of science and schooling as to change social conditions that changes people. Further the school subjects of mathematics and music education are explored as an alchemy, the use of translation tools that remake disciplinary knowledge into the school curriculum.  The alchemy of the curriculum is paradoxical.  It embodies cultural theses about kinds of people that inscribe differences and divisions in the name of inclusion and equity.